Inglourious basterds [a screenplay] - Tarantino, Quentin 1963- (Weinstein Books, 2009)
During World War II, a group of Jewish-American guerilla soldiers, led by Lt. Aldo Raine, become known as "The Basterds." They are chosen specifically to spread fear throughout the Third Reich by scalping and brutally killing Nazis. The Basterds soon cross paths with a French-Jewish woman who runs a movie theater in Paris which is targeted by the soldiers. A plot is set in motion to kill the Nazis at the theater's movie premier, including Adolph Hitler.
Keywords: Inglourious basterds (Motion picture); Inglourious basterds; Motion picture plays; Drehbuch